The Importance of Being Dead: Cell Death Mechanisms Assessment in Anti-Sarcoma Therapy - Rello-Varona, Santiago; Herrero-Martín, David; Lagares-Tena, Laura; López-Alemany, Roser; Mulet-Margalef, Núria; Huertas-Martínez, Juan; Garcia-Monclús, Silvia; García del Muro, Xavier; Muñoz-Pinedo, Cristina; Tirado, Oscar Martínez (Frontiers in Oncology, 2015)
Cell death can occur through different mechanisms, defined by their nature and physiological implications. Correct assessment of cell death is crucial for cancer therapy success. Sarcomas are a large and diverse group of neoplasias from mesenchymal origin. Among cell death types, apoptosis is by far the most studied in sarcomas. Albeit very promising in other fields, regulated necrosis and other cell death circumstances (as so-called ‘autophagic cell death’ or ‘mitotic catastrophe’) have not been yet properly addressed in sarcomas. Cell death is usually quantified in sarcomas by unspecific assays and in most cases the precise sequence of events remains poorly characterized. In this review our main objective is to put into context the most recent sarcoma cell death findings in the more general landscape of different cell death modalities.